2012
DOI: 10.1073/pnas.1213238109
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of serum antibodies reacting with simian virus 40 capsid protein mimotopes in patients affected by malignant pleural mesothelioma

Abstract: Human malignant pleural mesothelioma (MPM) is considered a rare tumor, but recent estimations indicate that one-quarter million people will die of this neoplasm in Europe in the next three decades. The mineral asbestos is considered the main causative agent of this neoplasm. MPM is largely unresponsive to conventional chemotherapy/radiotherapy. In addition to asbestos exposure, genetic predisposition to asbestos carcinogenesis and to simian virus (SV) 40 infection has also been suggested. SV40 is a DNA tumor v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 64 publications
5
72
1
1
Order By: Relevance
“…Moreover, some studies indicate a possible role of the simian virus (SV)40, which could act as a co-carcinogen of asbestos in mesothelioma development. 36 This could represent yet another mechanism of p53 inactivation through the interaction with the SV40 large T antigen. 37 Therefore, restoring p53 activity in mesothelioma, through direct pharmacological targeting, could be an effective antitumoral approach.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies indicate a possible role of the simian virus (SV)40, which could act as a co-carcinogen of asbestos in mesothelioma development. 36 This could represent yet another mechanism of p53 inactivation through the interaction with the SV40 large T antigen. 37 Therefore, restoring p53 activity in mesothelioma, through direct pharmacological targeting, could be an effective antitumoral approach.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were from our serum collections (23, 25, 27, 28). They were collected from pregnant women ( n  = 134) and non-pregnant women ( n  = 180) with a similar age.…”
Section: Methodsmentioning
confidence: 99%
“…We have not included measurement of polyomavirus Simian virus 40 (SV 40) seroprevalence in our study. Simian virus 40 seroprevalence has been reported to be anywhere between 9 and 12.7% in the general population and higher at 26% in patients with malignant mesothelioma in some studies (Poulin and DeCaprio, 2006; Mazzoni et al , 2012; Comar et al , 2014). However, other studies with conflicting results have shown that this low level seroprevalnce to SV40 is actually an artefact due to cross-reactivity with other related human polyomaviruses such as BKV and JCV (Poulin and DeCaprio, 2006; Kjaerheim et al , 2007; Shah, 2007).…”
Section: Discussionmentioning
confidence: 99%